Paradigma Baru Manajemen Pembelajaran MI dalam Menghadapi Tantangan Era Society 5.0 - Ahmad; Yessika Destiana Lahabu; Dila Nurlaila Zannah (Universitas Muhammadiyah Magelang, 2026)
This research aims to examine the new paradigm of learning management in Madrasah Ibtidaiyah in facing the challenges of the Society 5.0 era, especially in the aspect of integrating digital technology and Islamic values. The background of this research is based on the demands of educational transformation in the digital era which requires a paradigm shift in learning from teacher-centered to student-centered learning, as well as the importance of strengthening competencies in the 21st century. This research uses a qualitative approach with the type of case study carried out at MIN 1 Manado. Data collection techniques are carried out through observation, in-depth interviews, and documentation, while data analysis uses an interactive model that includes data reduction, data presentation, and conclusion drawn. The results of the study show that learning management in madrasas is still in the transition stage from a conventional approach to technology-based learning. Learning planning, implementation, and evaluation have not fully integrated technology systematically. Teachers' digital competence is still limited, so the use of technology in learning tends to be partial. In addition, the integration of Islamic values in learning has gone well, but it is not optimal in the context of digital learning. The various challenges faced include the limitations of teachers' competencies, facilities and infrastructure, as well as resistance to change. Therefore, efforts are needed to improve teachers' digital competence, strengthen madrasah policies, and develop adaptive and contextual learning models. This research makes a theoretical contribution to the development of Islamic learning management as well as a practical contribution to improving the quality of learning in the era of Society 5.0.